(untitled) (The Research of Medical Science Review, 2024)
Introduction: Chronic heart failure (CHF) is a major global health problem, affecting millions of people worldwide. Despite advances in the management of CHF, it remains a significant cause of morbidity and mortality. Objectives: The main objective of the study is to find the safety and tolerability of ARNI (SACUBITRIL VALSARTAN) in patients with chronic heart failure. Material and methods: The safety and tolerability of ARNI (sacubitril valsartan) in patients with chronic heart failure was assessed using a randomized, double-blind, placebo-controlled trial. Participants were selected based on established criteria for chronic heart failure and were excluded if they had a history of adverse reactions to either sacubitril or valsartan or had any contraindications to their use. Results: The results of the randomized, double-blind, placebo-controlled trial showed that ARNI was well-tolerated in patients with chronic heart failure. The incidence of adverse events, including serious adverse events, was similar between the ARNI and placebo groups. No significant differences were observed in blood pressure, heart rate, or laboratory values between the ARNI and placebo groups. The study was adequately powered to detect a clinically significant difference in adverse events, and statistical analysis showed no significant differences in adverse events between the two groups. Conclusion: In conclusion, the results of this study provide further evidence supporting the safety and tolerability of ARNI in patients with chronic heart failure. These findings, along with previous clinical trial and real-world data, support the use of ARNI as an effective and safe treatment option for patients with chronic heart failure.